2013
DOI: 10.1007/s00264-013-1915-4
|View full text |Cite
|
Sign up to set email alerts
|

Results of a French multicentre retrospective experience with four hundred and eighteen failed unicondylar knee arthroplasties

Abstract: Purpose By means of a multicentre retrospective study based on the failure of 418 aseptic unicondylar knee arthroplasties (UKA) our aims were to present the different types of revision procedure used in failed UKAs, to establish a clear operative strategy for each type of revision and to better define the indications for each type of revision.Methods Aseptic loosening was the principal cause of failure (n=184, 44 %) of which 99 cases were isolated tibial loosening (23.5 % of the whole series and 54 % of all lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…The reasons for revision in our study are consistent with published mechanisms of UKA failure [14,25,37,40,41], which include aseptic loosening, arthritis progression and unexplained knee pain. The most frequent reason for revision in our study was progression of OA.…”
Section: Discussionsupporting
confidence: 90%
“…The reasons for revision in our study are consistent with published mechanisms of UKA failure [14,25,37,40,41], which include aseptic loosening, arthritis progression and unexplained knee pain. The most frequent reason for revision in our study was progression of OA.…”
Section: Discussionsupporting
confidence: 90%
“…TKA is recommended for revision surgery after UKA [18]. Saragaglia et al [19] reported that TKA was conducted for revision surgery in 87% of 426 joints, (posterior stabilized(PS) type in 62.7%, CR type in 33.2%, and rotating hinge in 4.1%), while ipsilateral UKA was done in 7.7%, and they recommended TKA due to difficulty in using a similar implant for revision [19]. Our patient had a lateral bone defect with intact PCL, so revision surgery was performed with CR type TKA using augmentation and stem extension.…”
Section: Discussionmentioning
confidence: 99%
“…Still many published mechanisms of UKA failure [58,59] included aseptic loosening, arthritic progression, and unexplained knee pain. The most frequent causes of UKA failure are OA progression in other knee compartments and aseptic loosening of components [60].…”
Section: Revision Of Uka and Its Methodsmentioning
confidence: 99%